Evidence for music therapy and music medicine in psychiatry: transdiagnostic meta-review of meta-analyses - Alexander Lassner; Spyridon Siafis; Emanuel Wiese; Stefan Leucht; Susanne Metzner; Elias Wagner; Alkomiet Hasan (BJPsych Open)
Background Music therapy is a commonly used intervention added to usual care for psychiatric disorders.